Pengaruh Return On Assets, Debt To Equity Ratio, Total Assets Turn Over, Operating Cash Flow Dan Firm Size Terhadap Dividend Payout Ratio Pada Perusahaan Yang Terdaftar Di Jakarta Islamic Index (JII) Periode 2022 - Trizenda, Nadiyah; Frima, Rini; Sriyunianti, Fera (Pusat Penelitian dan Pengabdian Kepada Masyarakat, 2024)
The purpose of this research was to determine the effect of return on assets, debt to equity ratio, total assets turnover, operating cash flow and firm size on the dividend payout ratio of companies listed on the Jakarta Islamic index for the 2017-2021 period. There are 30 companies listed on the Jakarta Islamic index. The sampling technique used was purposive sampling so that 10 companies were used as samples in this study. Research data obtained from the website www.idx.co.id. The data analysis technique used panel data regression test. Data analysis using STATA 14 software. The results showed that return on assets had a positive effect on the dividend payout ratio, debt to equity ratio and total assets turnover had no effect on the dividend payout ratio, operating cash flow had a positive effect on the dividend payout ratio, and firm size had a negative effect on the dividend payout ratio. Return on assets, debt to equity ratio, total assets turn over, operating cash flow and firm size simultaneously affect the dividend payout ratio.